Implementation of the Principle of Justice in Islamic Inheritance Law in the Modern Era - Dila, Nadila; Faris, Mohammed Faris (Alhamdulillah : Jurnal Agama Islam, 2024)
This study discusses the implementation of the principle of justice in Islamic inheritance law in the modern era, with a focus on the challenges faced in its implementation in Indonesia. The principles of justice in Islamic inheritance law, such as proportional justice, fair distribution, social and economic justice, often experience obstacles due to changes in social, economic and family structures that continue to develop. Although Islamic inheritance law regulates the distribution of property by giving a larger share to men, challenges arise related to gender equality and the role of women in the family. In addition, the distribution of inheritance involving modern assets, such as stocks and cryptocurrencies, also requires adjustment. This study suggests the need for adjustments in the distribution of inheritance and increased understanding of Islamic inheritance law among law enforcement officers, so that the principles of justice can be implemented more fairly and relevant to current socio-economic conditions.